2008
DOI: 10.1101/gad.1656508
|View full text |Cite
|
Sign up to set email alerts
|

The conserved plant sterility gene HAP2 functions after attachment of fusogenic membranes in Chlamydomonas and Plasmodium gametes

Abstract: The cellular and molecular mechanisms that underlie species-specific membrane fusion between male and female gametes remain largely unknown. Here, by use of gene discovery methods in the green alga Chlamydomonas, gene disruption in the rodent malaria parasite Plasmodium berghei, and distinctive features of fertilization in both organisms, we report discovery of a mechanism that accounts for a conserved protein required for gamete fusion. A screen for fusion mutants in Chlamydomonas identified a homolog of HAP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
386
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(416 citation statements)
references
References 86 publications
15
386
0
Order By: Relevance
“…In spite of the many cellular events common to fertilization and zygote development in almost all eukaryotes, only recently was the first gamete-specific gene identified that is conserved and essential for fertilization in broadly disparate organisms. The gamete membrane protein HAP2(GCS1) is now known to be essential for gamete fusion in the isogamous, unicellular green alga Chlamydomonas; the unicellular malaria organism Plasmodium; and the higher plant Arabidopsis (Mori et al 2006;von Besser et al 2006;Hirai et al 2008;Liu et al 2008). Based on our results from Chlamydomonas and Plasmodium, the current model is that HAP2 is a gamete membrane fusogen in all three organisms and presumably in the many other protists, plants, and multicellular animals that possess it (Mori et al 2006;von Besser et al 2006;Hirai et al 2008;Liu et al 2010;Wong and Johnson 2010).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In spite of the many cellular events common to fertilization and zygote development in almost all eukaryotes, only recently was the first gamete-specific gene identified that is conserved and essential for fertilization in broadly disparate organisms. The gamete membrane protein HAP2(GCS1) is now known to be essential for gamete fusion in the isogamous, unicellular green alga Chlamydomonas; the unicellular malaria organism Plasmodium; and the higher plant Arabidopsis (Mori et al 2006;von Besser et al 2006;Hirai et al 2008;Liu et al 2008). Based on our results from Chlamydomonas and Plasmodium, the current model is that HAP2 is a gamete membrane fusogen in all three organisms and presumably in the many other protists, plants, and multicellular animals that possess it (Mori et al 2006;von Besser et al 2006;Hirai et al 2008;Liu et al 2010;Wong and Johnson 2010).…”
mentioning
confidence: 89%
“…The data shown are averages from three independent experiments, and the error bars are standard error of the mean (SEM). Transmission electron microscopy with 4-h and 7-h zygotes was performed as previously described (Liu et al 2008). …”
Section: Determination Of Nuclear Fusion Efficiencymentioning
confidence: 99%
“…While the exact proteins involved in initial binding of male and female gametes are yet unknown, gamete fusion is mediated by the microgamete protein GCS1 (generative cell specific 1; also termed HAP2), and disruption of the respective gene in P . berghei resulted in male sterility and blocked fertilization (Hirai et al ., 2008; Liu et al ., 2008). Following gamete fusion, nuclear fusion ensues, and over the next 3 h, meiosis occurs, and the zygote becomes tetraploid (Janse et al ., 1986), a process involving the NIMA‐related kinases Nek‐2 and Nek‐4 (Reininger et al ., 2005, 2009).…”
Section: The Formation Of Gametesmentioning
confidence: 99%
“…Interestingly, a generative cell specific 1 gene (GCS1), orthologous to HAP2, which was initially demonstrated to mediate membrane fusion of male and female gametes during fertilization in land plants (Mori et al 2006) and later identified as an ancestral gamete, fusogen, due to its high conservation among distantly related eukaryotes (Liu et al 2008, Wong and Johnson 2010, Speijer et al 2015, seems to be highly conserved among species of Chlorophyta.…”
Section: A Molecular Perspective On Fertility Genetic Controlmentioning
confidence: 99%